Astaxanthin protects against early acute kidney injury in severely burned rats by inactivating the TLR4/MyD88/NF-κB axis and upregulating heme oxygenase-1 - Songxue Guo (Nature Portfolio, 2021)
Abstract Early acute kidney injury (AKI) contributes to severe morbidity and mortality in critically burned patients. Renal inflammation plays a vital role in the progression of early AKI, acting as a therapeutic target. Astaxanthin (ATX) is a strong antioxidant widely distributed in marine organisms that exerts many biological effects in trauma and disease. ATX is also suggested to have anti-inflammatory activity. Hence, we attempted to explore the role of ATX in protecting against early postburn AKI via its anti-inflammatory effects and the related mechanisms. A severely burned model was established for histological and biochemical assessments based on adult male rats. We found that oxidative stress-induced tissue inflammation participated in the development of early AKI after burn injury and that the MyD88-dependent TLR4/NF-κB pathway was activated to regulate renal inflammation. The TLR4 and NF-κB inhibitors TAK242 and PDTC showed similar effects in attenuating burn-induced renal inflammation and early AKI. Upon ATX treatment, the release of inflammatory mediators in the kidneys was downregulated, while the TLR4/MyD88/NF-κB axis was inhibited in a dose-related manner. TAK242 and PDTC could enhance the anti-inflammatory effect of high-dose ATX, whereas lipopolysaccharide (LPS) reversed its action. Furthermore, the expression of heme oxygenase (HO)-1 was upregulated by ATX in a dose-related manner. Collectively, the above data suggest that ATX protects against renal inflammation in a dose-related manner by regulating the TLR4/MyD88/NF-κB axis and HO-1 and ultimately prevents early AKI following severe burns.